Investigation of Land Cover (lc)/Land Use (lu) Change Affecting Forest and Seminatural Ecosystems in Istanbul (turkey) Metropolitan Area Between 1990 and 2018 - Bozkurt, Selvinaz Gulcin; Kusak, Lutfiye; Akkemik, Unal (Springer, 2023)
This study was conducted to examine the land cover (LC)/land use (LU) change affecting forest and seminatural ecosystems and the spatio-temporal development of urban expansion between 1990 and 2018 in the city of Istanbul, where urbanization is the most intense in Turkey. For this purpose, using Corine Land Cover (1990, 2000, 2006, 2012, and 2018) dataset, the land cover of the area was determined in 5 different classes (artificial surface, agriculture, forest, water bodies, water), maps were produced, and tabular data were created. The changes in LC/LU between 1990 and 2018 were determined according to the Puyravaud land cover change rate and hot spot analysis methods. According to our findings, we determined that urbanization in Istanbul expanded the most in the east-west direction, and the agricultural and forest areas gradually decreased by 3.02% and 6.66% respectively; urban areas increased at the same rate of 9.69%. It is predicted that this change will continue increasing until 2030 when the forecasting method is applied in the field. It has been determined that the most important reasons for this situation are local government policies, population growth, and economic development initiatives applied in the area. As a result, it has emerged that measures should be taken based on sustainability and naturalness approaches to design urban development plans and to protect natural areas on a large scale, in order to limit possible LC/LU conversion from natural structure to urbanization in the area.
Akkemik, Unal/0000-0003-2099-5589; Bozkurt, Selvinaz Gulcin/0000-0003-0775-2005
Keywords: Natural Areas; Land Cover; Land Use; Geographical Information Systems; Hot Spot Analysis; Urbanization; Istanbul